Diagnóstico Del Esquema Corporal En Niños De Cinco A Once Años, En Cinco Colegios De La Ciudad De Armenia (2014)
This research, I seek to determine which children first grade, third and fifth grade were basic in their body schema; Was carried out by a diagnosis of body recognition, diagnosis of dynamic equilibrium and a battery of laterality was counted with a methodology to study descriptive research, which also counted with descriptive statistics was conducted in schools Laura Vicuna, Luis Carlos Galan Sarmiento, Junior Chamber, Normal Superior School of Quindío and Fitness English city of Armenia. This research threw that 25% of the study population has shortcomings with respect to the recognition of his own body; on the other hand on the state in which the children were with respect to its dynamic equilibrium found that 56% of these had problems maintaining good posture to help them maintain their balance while performing the activity and finally diagnosed in lateral predominance found that 64% of the study population has a cross laterality